2011
DOI: 10.1111/j.1365-2656.2011.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive responses to spatial and temporal prey availability in a coastal Arctic fox population

Abstract: Summary1. Input of external subsidies in the Arctic may have substantial effects on predator populations that otherwise would have been limited by low local primary productivity. 2. We explore life-history traits, age-specific fecundity, litter sizes and survival, and the population dynamics of an Arctic fox (Vulpes lagopus) population to explore the influence of the spatial distribution and temporal availability of its main prey; including both resident and migrating (external) prey resources. 3. This study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 44 publications
(100 reference statements)
5
58
0
Order By: Relevance
“…We found that both their diet and annual productivity were strongly affected by cyclic fluctuations in lemming abundance, as found elsewhere [69][70][71]. Even though lemming peaks may have been less pronounced during the 2000s than in the previous decade on Bylot Island, this had no long-term effect on fox productivity.…”
Section: Discussionmentioning
confidence: 65%
“…We found that both their diet and annual productivity were strongly affected by cyclic fluctuations in lemming abundance, as found elsewhere [69][70][71]. Even though lemming peaks may have been less pronounced during the 2000s than in the previous decade on Bylot Island, this had no long-term effect on fox productivity.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, food resource availability differs between the sites. Arctic foxes in Svalbard live in an ecosystem lacking small rodents and competitors (Fuglei et al 2003;Eide et al 2012), which is not the case in Russia (Pokrosvky et al 2014;Sokolov et al 2016). The scarcity and unpredictability of food resources in Svalbard makes the foxes behave as generalist scavengers, feeding opportunistically (Fuglei et al 2003;Eide et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Arctic foxes in Svalbard live in an ecosystem lacking small rodents and competitors (Fuglei et al 2003;Eide et al 2012), which is not the case in Russia (Pokrosvky et al 2014;Sokolov et al 2016). The scarcity and unpredictability of food resources in Svalbard makes the foxes behave as generalist scavengers, feeding opportunistically (Fuglei et al 2003;Eide et al 2012). One study in Svalbard showed that Arctic foxes had huge variation in fat content during winter (from 5% to 40% of skinned body mass; Prestrud & Nilssen 1992), indicating a need for an opportunistic search for food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a maximum age of 8 years in our population, while the oldest individuals were 7 or 8 years-old in other Canadian populations (Bradley et al 1981, Hiruki andStirling 1989), 8 years-old on Saint Lawrence Island in Alaska (Fay and Rausch 1992), and 10 years-old in Iceland (Hersteinsson 1992) and Svalbard (Eide et al 2012). This indicates that maximum longevity seems to be a rather constant parameter across arctic fox populations.…”
Section: Discussionmentioning
confidence: 87%